PEMAHAMAN IBU PADA LABELISASI HALAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK MAKANAN ANAK DI KECAMATAN KOTA SUMENEP - Destryana, R. Amilia; Ismawati, Ismawati; Wibisono, Aryo (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2019)
One of the issues of food today has spread throughout society is the issue ofhalal. In general, indicating the label of halal in the food products is on the package orthe label of the product that was officially published by Majelis Ulama Indonesia, MUI(The Indonesia Ulema Council). The role of the mother in child food product purchasingdecision is huge, especially for mothers who have children ages 1-12 years. At the age ofthe child, mother tends to be protective in buying children's meals because of securityconcerns from religious or health aspects for a Muslim. It is one of district in Maduraisland with a majority Muslim population, is Sumenep. This research aims to know themother's understanding on halal label on the food product packaging and theidentification of its influence on the purchase of food products, with the dependentvariables consists of understanding the mother against halal label, price and productquality in children's meals and independent variables in the form of purchase decisions.Instrument research using enclosed questionnaires. The indicators used in determiningthe level of understanding of mothers towards halal labels refer to the halal definitionbased on LPPOM-MUI, the official halal logo issued by MUI. The data were analyzedusing descriptive analysis of the characteristics of respondents and multiple linearregression analysis. The results showed that mother enough understand about children'sfood products labeled halal, considered the understanding is already good. Variablesthat have a significant influence on the selection of a child's food product are halal labelvariables. The halal label, price and product quality are the main factors that influencemothers in deciding to buy children's food products in Sumenep.